Synthesis and physicochemical studies of fluconazole ionic liquids - Vaishnavi Mangrule, Yogesh Pore, John Disouza (Journal of Applied Pharmaceutical Science, 2017)
Active pharmaceutical ingredient (API) based ionic liquids (ILs) were synthesized by combination of cationic fluconazole (FLC) and anionic ascorbic acid. The solid form of the low water soluble API was converted into its liquid salt form to improve physicochemical properties and evaluate biological activity. ILs were synthesized in different molar ratios of FLC- ascorbic acid (1:1 and 1: 2.5) by applying solvent evaporation method with methanol as the solvent. The analytical evidences for the formation of ILs were generated and confirmed by differential scanning calorimetry (DSC), Fourier transformation-infrared spectroscopy (FTIR) and X-ray powder diffractometry (XRPD). The solubility and dissolution of 1:1 and 1:2.5 ILs were significantly improved as compared to FLC alone, supported by decreased log P values. The improvement of physicochemical properties of IL 1:1 was found to be reliable as compared to the IL 1: 2.5. The antifungal activity of IL 1:1 was retained against Candida albicans. However, increasing the molar ratio of ascorbic acid resulted in reduction of activity.
Keywords: Fluconazole, ionic liquids, ascorbic acid, physicochemical, antifungal activity.